Technological innovation in the ambience of facilities for farm animals: Applications - Melo, Gabriel Maurício Peruca de; Bertipaglia, Liandra Maria Abaker; Melo, Wanderley José de; Bardi, Cassia Cristina Tannuri Gomes; Pereira, Luiz Arthur Malta; Zeferino, Cynthia Pieri; Dian, Paulo Henrique Moura (Seven Editora, 2024)
The chapter discusses the progress of science and technology in facilities for farm animals. It is noteworthy that technological innovations often surpass science’s ability to assimilate them quickly, especially with the exponential growth of databases. The text contextualizes the evolution of animal facilities throughout history. In the past, the focus was on physical elements and equipment to control the microclimate, but with technological advancements, the introduction of artificial intelligence (AI) has revolutionized the way these environments are planned and managed. AI enables real-time data collection, analysis, and interpretation, making it possible to make precise adjustments to environmental conditions to meet the needs of animals. Technology has evolved to record animal activities that may be related to health, including movements, behaviors, and vital signs. Despite the advances, the text points out structural and biological challenges that may hinder the implementation of new technologies in facilities. However, the importance of facility planning to ensure animal welfare and productivity is highlighted, especially when considering thermal comfort. This involves understanding the specific needs of animals in relation to the environment, choosing suitable building materials, and adopting sustainable practices such as renewable energy systems. In short, the chapter emphasizes that the revolution in the ambience of animal facilities, driven by artificial intelligence, represents a significant advance in the search for adaptable and optimal conditions, creating a healthier and more efficient environment for animal production. DOI:https://doi.org/10.56238/sevened2023.006-157